Forgetting Egypt's Ottoman Past - Toledano, Ehud (Jama'a: an Interdisciplinary Journal of Middle East Studies, 1997)
The study focuses on Egypt's national memory, history and historiog- raphy. It shows how Egypt's Ottoman past has been erased from the collective memory of the Egyptian community. A reevaluation of Egypt's national memory came hand in hand with the emergence of a new national identity in the country. Reconstructing Egypt's collective memory had a significant impact on the identity of the Ottoman- Egyptian elite. Amnesia served as a means of legitimizing the Egyptian monarchical regime as an organic institution inexorably linked to the destiny of the Egyptian nation.